Multiple Pyogenic Spondylodiscitis with Bilateral Psoas Abscesses Accompanying Osteomyelitis of Lateral Malleolus - A Case Report - - Lee, Bong-Jin (Korean Society of Spine Surgery, 2008)
A psoas abscess is a potentially life-threatening infection. Multiple pyogenic spondylodiscitis with bilateral psoas abscesses accompanying an osteomyelitis of the lateral malleolus is an extremely rare event. We present our experience with needle aspiration for the treatment of osteomyelitis of the lateral malleolus and CT-guided percutaneous catheter drainage for a psoas abscess in an elderly patient. Both infections were completely resolved without recurrence. A psoas abscess should be included in the differential diagnosis of a patient with low back pain during musculoskeletal infection. Percutaneous needle aspiration or CT-guided percutaneous catheter drainage is an effective method for treating certain musculoskeletal infections.